Fast construction of isoquinolin-1(2H)-ones by direct intramolecular C–H/N–H functionalization under metal-free conditions. Issue 2 (13th December 2019) - Wen, Li-Rong; Ren, Guang-Yi; Geng, Rui-Sen; Zhang, Lin-Bao; Li, Ming
Abstract : Polycyclic six-, seven- and eight-membered N-heterocycles can be rapidly synthesized employing PIDA under metal-free conditions within 1 min. Abstract : The general protocol for the synthesis of isoxazolidine-fused isoquinolin-1(2 H )-ones was established with the help of bench stable hypervalent iodine reagent PIDA. Polycyclic six-, seven- and eight-membered N-heterocycles can be rapidly synthesized from available amides under metal-free conditions within 1 min at room temperature through C–H/N–H functionalization. Moreover, the protocol has the merits of broad substrate scope, atom economy and operational simplicity.